2021
DOI: 10.1002/tpg2.20132
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression analysis of pigeonpea with male sterility conditioned by A2 cytoplasm

Abstract: Cytoplasmic male sterility(CMS), a maternally inherited trait, provides a promising means to harness yield gains associated with hybrid vigor. In pigeonpea [Cajanus cajan (L.) Huth], nine types of sterility-inducing cytoplasm have been reported, of which A 2 and A 4 have been successfully deployed in hybrid breeding. Unfortunately, molecular mechanism of the CMS trait is poorly understood because of limited research invested. More recently, an association between a mitochondrial gene (nad7) and A 4 -CMS has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The study by Raju et al (2010) reported 9,468 high quality ESTs and identified genes responsive to Fusarium wilt ( 19) and sterility mosaic disease (20), the two most prominent diseases of pigeonpea. More recently, transcriptome assemblies have been developed in pigeonpea based on RNA-Seq of transcriptomes from unopened flower buds of male sterile lines and cognate fertile lines (Bohra et al 2021a, Bohra et al 2021b.…”
Section: Transcriptomic Resources In Pulsesmentioning
confidence: 99%
“…The study by Raju et al (2010) reported 9,468 high quality ESTs and identified genes responsive to Fusarium wilt ( 19) and sterility mosaic disease (20), the two most prominent diseases of pigeonpea. More recently, transcriptome assemblies have been developed in pigeonpea based on RNA-Seq of transcriptomes from unopened flower buds of male sterile lines and cognate fertile lines (Bohra et al 2021a, Bohra et al 2021b.…”
Section: Transcriptomic Resources In Pulsesmentioning
confidence: 99%
“…The trait is widespread in flowering plants, with more than 140 species known to exhibit CMS [7]. These include maize, sunflower, sorghum, common beans, cotton, rice, pigeonpea, pepper, and wheat [8][9][10][11][12]. The CMS phenomenon provides a convenient model to study nuclear-cytoplasmic interactions, but its molecular mechanism is very complex [13,14].…”
Section: Introductionmentioning
confidence: 99%